How to report misinformation on social media platforms - Friesen, Kelsey; Boulianne, Shelley; Belland, Stephanie (My University, 2021)
These infographics offer step by step instructions about how to report misinformation on Facebook, Instagram, WhatsApp, Twitter, Reddit, Snapchat, YouTube, and TikTok. This infographic also highlights key findings from a four-country (USA, UK, France, Canada) survey conducted in February 2021.
Keywords: misinformation; social media